2006
DOI: 10.1016/j.cell.2006.04.040
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mousetrap Determines Polarity of Termination of DNA Replication in E. coli

Abstract: During chromosome synthesis in Escherichia coli, replication forks are blocked by Tus bound Ter sites on approach from one direction but not the other. To study the basis of this polarity, we measured the rates of dissociation of Tus from forked TerB oligonucleotides, such as would be produced by the replicative DnaB helicase at both the fork-blocking (nonpermissive) and permissive ends of the Ter site. Strand separation of a few nucleotides at the permissive end was sufficient to force rapid dissociation of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
173
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(184 citation statements)
references
References 34 publications
(74 reference statements)
10
173
1
Order By: Relevance
“…Tus F140A fails to support an efficient "lock" mechanism when the Ter site is partially single stranded at the non-permissive end, because it cannot accommodate the base-flipped Ter-C6 residue. 14 However, Tus F140A exhibits a higher affinity than wtTus for duplex Ter 14 Larsen et al found that wtTus mediates polar replication fork arrest at a Ter array in S. cerevisiae. 22 The same authors found that Tus F140A is unable to generate an efficient replication fork barrier when bound to a chromosomal Ter array in S. cerevisiae, even when the majority of replication forks arrive at the non-permissive face of Tus/Ter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tus F140A fails to support an efficient "lock" mechanism when the Ter site is partially single stranded at the non-permissive end, because it cannot accommodate the base-flipped Ter-C6 residue. 14 However, Tus F140A exhibits a higher affinity than wtTus for duplex Ter 14 Larsen et al found that wtTus mediates polar replication fork arrest at a Ter array in S. cerevisiae. 22 The same authors found that Tus F140A is unable to generate an efficient replication fork barrier when bound to a chromosomal Ter array in S. cerevisiae, even when the majority of replication forks arrive at the non-permissive face of Tus/Ter.…”
Section: Discussionmentioning
confidence: 99%
“…By placing the 6xTer array within a reporter of mammalian HR, targeted to a specific locus of mouse embryonic stem (ES) cells, we found that transient expression of wild type Tus triggers HR at the 6xTer array, while expression of a mutant form of Tus (H144A) that has a low affinity for Ter failed to induce HR in the same cells. 14,15 Several lines of evidence indicate that Tus/Ter-induced HR in mammalian cells entails the processing of 2 converging forks arrested at the Tus/Ter fork block. Tus/Ter-induced HR predominantly generates "short tract" gene conversions (STGC)-a conservative HR outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms4574 ARTICLE characterized C-T substitution 22 in each of the TerB sites adjacent to ARS305 abolished RF pausing ( Supplementary Fig. 2).…”
Section: Tus-ter Modules Cause Polar Rf Pausing In Yeast the 21-bpmentioning
confidence: 99%
“…Two models have been proposed to explain how Tus-Ter functions as a polar RF barrier in E. coli. The 'mousetrap' model of Tus-Ter RF pausing posits that a specific interaction is required between Tus and a critical 'locking cytosine' residue within TerB that is revealed by DNA strand separation 22 . An alternative model proposes that RF arrest at Tus-Ter is mediated by specific protein-protein interactions in E. coli 23,24 .…”
Section: Tus-ter Modules Cause Polar Rf Pausing In Yeast the 21-bpmentioning
confidence: 99%